(untitled) (European Journal of Pure and Applied Mathematics, 2025)
The interaction between cancer and HIV underscores the paramount significance of immune response mechanisms in both diseases, illuminating the necessity for tailored management and treatment approaches to address cancer in individuals living with HIV. In this study, a mathematical model is formulated to conceptualize the interaction between HIV and tumors in relation to the immune system’s response. The basic theory and concepts of the Caputo-Fabrizio operator are presented to analyze the recommended dynamics. The dynamics of HIV and tumor interactions in the context of immune response are systematically investigated. A numerical scheme is developed to examine the suggested system and to assess the role of various input factors on the dynamics. The numerical results delineate key parameters that govern the complex phenomena between HIV-tumor and immune dynamics, offering crucial insights that can inform public health interventions and treatment strategies.